Notices of the Discovery of a Cist and Urns at Juniper Green, and of a Cist at The Cunninghar, Tillicoultry, and of some undescribed Cup-marked Stones - Coles, Frederick R (Proceedings of the Society of Antiquaries of Scotland, 1899)